Examining a transdiagnostic measure of repetitive thinking in depressed, formerly depressed and never-depressed individuals - Samtani, S.; McEvoy, Peter; Mahoney, A.; Werner-Seidler, A.; Li, S.; McGill, B.; Tockar, J.; Moulds, M. (Elsevier BV, 2018)
BACKGROUND: Evidence that repetitive negative thinking (RNT) is a shared feature of a number of disorders has prompted the need for transdiagnostic self-report instruments; that is, measures of RNT that can be administered to individuals irrespective of their diagnosis. The Repetitive Thinking Questionnaire (RTQ; McEvoy et al., 2010) was developed to meet this need, and its psychometric properties and capacity to predict psychopathology have been tested in undergraduate and clinically anxious samples. METHODS: We administered the RTQ to currently depressed (n = 29), formerly depressed (n = 61) and never-depressed (n = 93) community participants. RESULTS: The RTQ demonstrated good psychometric properties, with excellent internal consistency for the RNT subscale (a=.93) and good convergent validity with measures of negative affect and psychopathology symptoms (rs= .47-.61). In addition, and in accord with our predictions, currently depressed and recovered depressed participants reported more RNT than never-depressed participants, but currently and recovered depressed participants did not differ. In addition, RNT scores explained additional variance in depression and anxiety symptoms, after controlling for gender, age, neuroticism, state negative affect, and intolerance of uncertainty. LIMITATIONS: Our sample was drawn from the community but participants were not treatment-seeking, and we employed a cross-sectional design. DISCUSSION: Taken together with previous experimental and longitudinal studies, our results support the utility of addressing RNT in the treatment and prevention of relapse in depression. Moreover, these data confirm the utility of the RTQ as a brief, transdiagnostic self-report measure of RNT.